2018
DOI: 10.1021/acsnano.8b08260
|View full text |Cite
|
Sign up to set email alerts
|

Gate-Controlled Metal–Insulator Transition in TiS3 Nanowire Field-Effect Transistors

Abstract: We explore the electrical characteristics of TiS 3 nanowire field-effect transistor (FETs), over the wide temperature range from 3 to 350 K. These nanomaterials have a quasi-one-dimensional (1D) crystal structure and exhibit a gate-controlled metal−insulator transition (MIT) in their transfer curves. Their room-temperature mobility is ∼20−30 cm 2 /(V s), 2 orders of magnitude smaller than predicted previously, a result that we explain quantitatively in terms of the influence of polar-optical phonon scattering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
106
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(137 citation statements)
references
References 60 publications
27
106
2
2
Order By: Relevance
“…1c). We find an n-type semiconducting behavior similar to earlier reports [1,4,15]. The ON/OFF ratio appears to be small ∼ 2.3, while the threshold voltage is about −30 V from the onset of conductivity, indicating that large residual doping is responsible for the large current in the OFF state, in agreement with previous studies [4].…”
supporting
confidence: 92%
“…1c). We find an n-type semiconducting behavior similar to earlier reports [1,4,15]. The ON/OFF ratio appears to be small ∼ 2.3, while the threshold voltage is about −30 V from the onset of conductivity, indicating that large residual doping is responsible for the large current in the OFF state, in agreement with previous studies [4].…”
supporting
confidence: 92%
“…[15,16] MS 3 is considered to have great potential in application of optical and electronic devices because of its unique quasi-1D crystal structure and strong optical anisotropy. [11,[17][18][19][20][21][22] Previous studies have shown that the dichroic ratio of TiS 3 is 4:1 [16] and that of ZrS 3 is 2.55:1. [15] The best excitation energy of the dichromatic ratio generated by photocurrent was 1.00-2.0 eV for TiS 3 and 2.0 to 3.0 eV for ZrS 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 15,16 ] MS 3 is considered to have great potential in application of optical and electronic devices because of its unique quasi‐1D crystal structure and strong optical anisotropy. [ 11,17–22 ]…”
Section: Introductionmentioning
confidence: 99%
“…While a considerable number of in vitro and in vivo studies have focused on the assessment of toxicity of graphene-based materials [9,10], other 2D materials have received much less attention from researchers. For example, there have been no nanotoxicity studies of materials from a large family of transition metal trichalcogenides (TMTCs) with the general formula MX 3 (M = Ti, Zr, Hf, Nb or Ta; X = S, Se or Te) [11][12][13][14], which have recently received much attention due to their promising electronic [15][16][17][18][19][20] and optoelectronic [21,22] and thermoelectric properties [23][24][25]. The crystal structure of TMTC materials is different from other 2D materials, which is shown in Figure 1a using ZrS 3 as an example [11][12][13][14]26].…”
Section: Introductionmentioning
confidence: 99%